From China to the Dutch East Indies: Colonial Opium Control and Indonesian Narcotics Law - Andri Winjaya Laksana (Sriwijaya Law Review, 2026)
This study examines the historical foundations of Indonesian narcotics law without assuming a direct causal line from the British opium trade in China to Law No. 35 of 2009. The problem is the tendency of legal-historical accounts to treat China and Indonesia as equivalent colonial experiences and omit the stages through which international drug control was received in the Dutch East Indies and post-independence Indonesia. Using doctrinal legal research, legal history, and conceptual analysis, the study develops a connected-history framework that distinguishes origin, transmission, colonial reception, and domestic adaptation. The findings show that British intervention in China functioned as an international catalyst by exposing the conflict between commercial power, regulatory sovereignty, and public health. The 1909 Shanghai Opium Commission and the 1912 International Opium Convention converted that controversy into multilateral control techniques, while the Dutch Opiumregie supplied the more direct administrative link to Indonesian territory. Indonesia’s punitive orientation cannot therefore be attributed solely to Britain or China; it also reflects later United Nations conventions, post-independence legislation, enforcement practices, and national policy choices. Continuity is strongest at the functional level—classification, licensing, surveillance, and penal control rather than as an unbroken transfer of identical legal rules. The article proposes a differentiated enforcement model that preserves firm sanctions for organized trafficking while making assessment, medical and social rehabilitation, and reintegration the primary response for addicts and victims of abuse, particularly young people. Its novelty lies in a four-stage transmission model that clarifies the relevance and limits of colonial genealogy for reforming Indonesian narcotics law.